The Effectiveness of Interventions in Improving Hand Hygiene Compliance: A Meta-Analysis and Logic Model - Mohammad Hossein Kaveh; Mohadeseh Motamed-Jahromi; Soheil Hassanipour (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Despite the availability of various guidelines, rules, and strategies, hand hygiene adherence rates among healthcare workers are reported significantly lower than expected. The aim of this meta-analysis is to determine the most effective interventions to improve hand hygiene and to develop a logic model based on the characteristics of the most effective interventions. Methods. A literature search was conducted on PubMed, ProQuest, Web of Knowledge, Scopus, Cochrane Library, and ScienceDirect databases up to December 21, 2019, with no time limit. Randomized clinical trials which had designed interventions to improve hand hygiene were reviewed. Data were extracted independently by two authors. All statistical analyses were performed using Comprehensive Meta-Analysis (CMA) software (version 2.0). A random-effects model was used to estimate odds ratios. Results. Although 14 studies were initially reviewed, only 12 studies entered the meta-analysis, since they had identified percentage rates of hand hygiene compliance. The most effective intervention (odds ratio 18.4, 95% CI (13.6–24.8)) was a multilevel strategy that influenced the determinants of hand hygiene behavior at individual, interpersonal, and organizational levels. Following this, a theory-driven logic model was mapped out to promote hand hygiene, based on situational analysis. Conclusion. This study suggests that designing integrated interventions based on a multilevel socioecological approach has the greatest potential to improve hand hygiene compliance in healthcare workers. The logical model proposed in this study can thus provide a useful guide for designing and conducting future experimental research.